Hepatocellular Carcinoma with Prominent Intracytoplasmic Inclusions: A Report of Two Cases - Adeline R. Chelliah; Jasim M. Radhi (Case Reports in Hepatology)
Hepatocellular carcinoma (HCC) is the commonest primary malignant neoplasm of the liver in most countries with a notoriously poor prognosis. Variation in global incidence is well-recognized and the occurrence of HCC is linked to several established environmental, dietary, and lifestyle factors. HCC demonstrates morphological heterogeneity both within the same tumor and from patient to patient. Differing architectural patterns and cytological variants may be seen. Inclusion bodies are believed to represent organized structures of proteins which contribute to their pathogenesis and share several constituents like chaperones, p62, ubiquitin, and Valosin containing protein. The various hepatocyte cytoplasmic inclusions described in HCC include Mallory-Denk bodies (MDBs), hyaline bodies (HBs), glycogen, fat, fibrinogen, alpha 1 antitrypsin (AAT), and ground glass. MDBs are the most common inclusions seen in hepatocellular carcinomas. The two cases shared intracytoplasmic inclusions which are characterized by larger sizes and present in every section examined. These exhibited features of MDBs and HBs present in most tumor cells, further supporting close relationship.